RAISING AWARENESS ON CLASSROOM INTERACTION COMPETENCE THROUGH SETT - Demirbuken, Buket; Mutlu-Gülbak, Gizem (English Language Education Study Program Association (ELESPA) or Asosiasi Program Studi Pendidikan Bahasa Inggris (APSPBI), Indonesia, 2025)
This case study aimed at raising teacher awareness of classroom interactional competence regarding pedagogical goals and interactional features in Walsh’s (2003) Self Evaluation Teacher Talk (SETT) framework. To this end, the data were obtained from an in-service EFL teacher’s video-recorded teaching in two main phases: 1) the teacher’s four hours of classes were analyzed to characterize the modes by the researchers, after which the teacher was informed about the modes and SETT framework in an interview, and 2) the teacher was self-reflected on his another four hours of teaching by characterizing the modes. The findings analyzed through content analysis revealed that the meetings were insightful in fostering teachers’ awareness of classroom interaction skills since the teacher performed a high level of accuracy in characterizing classroom modes and the deployment of related terminology. In addition, self-talk had a positive contribution to the reflection process, enabling a dialogue on troubles in classroom interaction and the teacher’s resistance with justification in dialogues signposted a need to highlight the value of dialogue besides teacher awareness.